Globalization and liberalization in the Malaysian construction industry - Ab. Rani, Nur Izzati (2015)
As a developing country, Malaysia has been gone through a lot of development works in the country. These activities give positive impact on the growth of the Malaysian economy. Globalization and liberalization have taken part in this growth by bringing in foreign direct investment (FDI) especially to the construction industry. As a result of the globalization and liberalization, the Malaysian government has signed free trade agreements (FTA) either the regional or bilateral free trade agreements. This paper which is undertaken via literature review aims at appraising globalization and liberalization in the Malaysian construction industry through the identification of the impacts of globalization and liberalization in construction industry by looking at the FTA signed by the Malaysian government from the perspectives of foreign contractors’ registration and project by foreign contractors. This paper shows the trend of the current foreign firm participation in the Malaysian construction industry of which the Malaysian government can promote various development programs for local contractors in giving positive competition to foreign firms in the Malaysian construction industry.